Final Cut Express 2 Editing Workshop, 2nd Edition - Wolsky, Tom (Focal Press, 2013)
Nonlinear, or digital, editing involves the manipulation of digitized video. Software applications permit the editor to cut, splice, make transitions, and edit film more precisely than was ever possible with conventional film editing techniques. Final Cut Express 2 is an inexpensive version of Apple's Final Cut Pro software, the leading nonlinear editing program for the Mac platform. In its first year, Final Cut Express proved to be a compelling alternative for hobbyists, students, and professionals who had formerly been limited to iMovie. Final Cut Express 2 Editing Workshop is a classroom-in-a-book that teaches readers the art and technique of editing with Final Cut Express 2. It features a series of tutorials that cover the complete range of tasks, from installing the application to outputting. All of the necessary materials, including raw video footage and sequences, detailed instructions, and techniques taught in film schools, guide the reader to a working knowledge of Final Cut Express 2. The companion DVD includes a video introduction to Final Cut Express 2 specially designed for iMovie users, as well as tutorial media and plug-ins.